ANALISIS PENGUATAN KARAKTER MANDIRI MELALUI KEGIATAN PEMBIASAAN DI LINGKUNGAN SEKOLAH PADA PESERTA DIDIK KELAS IV SDN GUNUNGDATAR PANDEGLANG - Oktovianti, Mimah; Nurhasanah, Ana; Adya Pribadi, Reksa (Jurnal Pendidikan Dasar, 2024)
Education plays an essential role in shaping a generation of individuals with strong character, including instilling independence from an early age. Independent character is a crucial foundation for building responsible, disciplined, and integrity-driven individuals. This study aims to analyze the strengthening of independent character through habituation activities in the school environment for fourth-grade students at SDN Gunungdatar, Pandeglang. A descriptive qualitative approach was employed, with the research subjects being fourth-grade teachers and students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman method, which includes data reduction, data presentation, and conclusion drawing. The findings show that habituation activities, such as reciting prayers, performing class duties, and completing tasks independently, have successfully created a conducive learning environment. Teachers serve as role models, while support from schools and parents strengthens these habituation activities. Challenges include the lack of parental involvement and limited school facilities. Nevertheless, the impact is significant, with students becoming more independent, responsible, and capable of completing tasks without relying on others. This study emphasizes the importance of collaboration among teachers, parents, and schools in fostering independent character through sustainable habituation programs, making a tangible contribution to character education for students.